Neuroplasticity and Functional Recovery Following Brain Injury - Stevupta, Mathew (Journal of Contemporary Medical Practice, 2025)
“Traumatic Brain Injury (TBI)” is stimulating for both diagnosis and treatment. It consists of physiological or structural injuries in brain function along with external forces. These injuries may cause formation of gliotic scar, cellular death, and damage from inflammation and reactive oxygen. A lot of research attention has been given to external influencers to promote neuroplasticity with significant effects on neurologic injury treatment. A lot of these methods and existing studies are reviewed in this study. With advancements in neuroscience, an in - depth knowledge of the intricacy of interconnection in the brain and its capability to adapt to the environment is “promoting neurorehabilitation which augments the capacity of brain to adapt with neuroplastic change”. This systematic review has been conducted to explore the benefits of innovative technologies used for neurorehabilitation of patients suffering from brain injury. There has been a rise in recognition and appreciation of neuroplasticity which has brought modern approaches to encourage neuro - recovery, which boosts stimulation and secretion of neutrophic factors. Some of the modern approaches are non - invasive stimulation, pharmacologic agents, task - based and aerobic exercise, mirror therapy, and improvement of sleep. Future studies are needed to build the foundation of therapeutic techniques and rehabilitation to promote natural healing of brain and functional results.